Static, vibration and buckling analysis of skew composite and sandwich plates under thermo mechanical loading - Singh, Shantanu Kumar; Chakrabarti, Anupam (Zielona Góra: Uniwersytet Zielonogórski)
Static, vibration and buckling behavior of laminated composite and sandwich skew plates is studied using an efficient C0 FE model developed based on refined higher order zigzag theory. The C0 FE model satisfies the inter-laminar shear stress continuity at the interfaces and zero transverse shear stress conditions at plate top and bottom. In this model, the first derivatives of transverse displacement have been treated as independent variables to overcome the problem of C1 continuity associated with the plate theory.
Keywords: skew plates; finite element; refined theory; thermal load